Seasonal use of waterholes and pathways by macrofauna in the dry forest of Costa Rica - Guimarães Rodrigues, Flavio Henrique (2019)
Temporal and spatial scarcity of water in semi-arid and seasonal ecosystems often leads to changes in movements and behaviour of large vertebrates, and in the neotropics this dynamic is poorly understood due to logistical and methodological limitations. Here we used camera trapping to elucidate variation in patterns of seasonal use of waterholes and pathways by 10 large-mammal and four large-bird species in the dry forest of north-western Costa Rica. From 2011 to 2015, we deployed trail cameras at 50 locations, including waterholes and three types of pathway (roads, human trails and animal paths). We used Generalized Linear Models to evaluate the effect of location and seasonality on the rates at which independent photographs were taken. We found interacting effects of location and seasonality for the capuchin monkey (Cebus capucinus), the tiger heron (Trigrisoma mexicanum), the white-tailed deer (Odocoileus virginianus) and the tapir (Tapirus bairdii) suggesting that these species were the most influenced by waterholes during the dry season. Comparison of waterhole sites and specific types of pathways (roads, animal paths and human trails) showed that location influenced photo-capture rates of almost all species, suggesting a useful insight to avoid and account for bias in camera trap studies. Furthering our ecological understanding of seasonal water regimes and large vertebrates’ behaviours allow for better understanding of the consequences of climate change on them.